2017
DOI: 10.17576/jsm-2017-4610-24
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nociceptive Effect of Caralluma edulis on Peripheral and Central Pain Pathways

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[11][12][13] The extracts of C. edulis are reported to have antioxidant, antidiabetic, antinociceptive, antiinflammatory and hunger suppressant effects. [14][15][16][17] The current study was designed to evaluate CE.Cr for its potential against obesity, hypertension, atherosclerosis and oxidative stress, and to provide scientific evidence for its folkloric uses.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The extracts of C. edulis are reported to have antioxidant, antidiabetic, antinociceptive, antiinflammatory and hunger suppressant effects. [14][15][16][17] The current study was designed to evaluate CE.Cr for its potential against obesity, hypertension, atherosclerosis and oxidative stress, and to provide scientific evidence for its folkloric uses.…”
Section: Introductionmentioning
confidence: 99%
“…In multiple ethnobotanical reports, it was found that natives consume it in various forms for the management of diabetes mellitus (Ahmad, Khan, Arshad, & Zafar, 2006;Ahmad, Qureshi, Arshad, Khan, & Zafar, 2009;Malik et al, 2015;Yaseen et al, 2015). The extracts of C. edulis are reported to have antioxidant (Shad, Bakht, Shah, & Hayat, 2016), antidiabetic (Sayantan & Abhishek, 2012), antinociceptive (Firdoos, Khan, & Ali, 2017), antiinflammatory (Minhas, Khan, & Ansari, 2018), antihyperlipidemic (Ashfaq et al, 2017), and hunger suppressant effects (Surveswaran, Cai, Xing, Corke, & Sun, 2010). The chemical composition of C. edulis disclosed β-sitosterol, magasatgmane, glycosides, steroidal glycosides, saturated pregnane steroids, and flavonoids (Abdel-Sattar et al, 2008;Memon & Bhatti, 1984).…”
mentioning
confidence: 99%